Ocurrencia de enfermedades y acciones de sanidad animal :(sistema de información de sanidad animal - SINSA) 1991 - Díaz Martínez, Olga Lucía; Zuñiga Arce, Ismael; López Castaño, Miguel Angel; Urbina Amaris, Mario Enrique (ICA, 2018)
Salud animal